Analysis of Transpolitan Program Development to Improve Superior Commodities Through the Role of BUMDes in Batu Betumpang Village, South Bangka Regency - Karil Maulita; Dini Hariyanti; Mona Adriana S (Dinasti Publisher, 2025)
This research analyzes the development of the Transpolitan Program aimed at enhancing leading commodities through the role of the Village-Owned Enterprise (BUMDes) in Batu Betumpang Village, South Bangka Regency. This village is one of the 52 National Priority Transmigration Areas with significant potential in agricultural, plantation, and fishery commodities, yet it faces challenges in optimization. The objectives of this study are to (1) analyze the influence of the Transpolitan Program on the development of leading commodities, (2) examine the role of BUMDes in the development of these commodities, (3) analyze the level of community financial literacy, and (4) formulate strategies and policy recommendations to strengthen the program. The method used is qualitative research with a descriptive approach. Primary data were collected through in-depth interviews and Focus Group Discussions (FGDs) with stakeholders, including the village government, BUMDes management, and community representatives. The collected data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and mapped onto a SPACE matrix to determine the strategic position. The research findings indicate that Batu Betumpang Village possesses significant strengths in the diversity and potential of its leading commodities, particularly rice, palm oil, and fisheries, supported by the national food self-sufficiency program. However, this development is hampered by serious structural weaknesses, such as the absence of an adequate irrigation dam, minimal road infrastructure, and a lack of local post-harvest processing facilities. The role of the BUMDes is identified as important in managing village assets and providing limited capital, but it is not yet optimal due to managerial constraints, a lack of innovation, and weak coordination. The community's financial literacy level shows foundational potential but is threatened by limited digital access and the risk of financial fraud. The SPACE matrix analysis places Batu Betumpang Village in the Aggressive quadrant, indicating that the village has strong internal strengths and external opportunities to proactively address existing weaknesses and maximize its growth potential.